2008
DOI: 10.2106/jbjs.f.01515
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Surgical Site Infection Following Orthopaedic Spinal Operations

Abstract: Victoria J., "Risk factors for surgical site infection following orthopaedic spinal operations". The Journal of Bone and Joint Surgery, 90, 1, 62-69. 2008 Background: Surgical site infections are not uncommon following spinal operations, and they can be associated with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
467
14
24

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 689 publications
(530 citation statements)
references
References 24 publications
25
467
14
24
Order By: Relevance
“…Five additional potentially relevant studies were identified from reference lists. Of the 34 articles that underwent full-text review, 12 [22][23][24][25][26][27][28][29][30][31][32][33] met eligibility criteria for inclusion in the meta-analysis and 22 were excluded. The most common reasons for exclusion of the 22 studies were: criteria for the diagnosis of SSI not reported and/or CDC/NNIS criteria not applied [34][35][36][37][38][39][40][41][42][43][44][45][46][47], non-scalar definitions of obesity used [47][48][49], risk estimates of the association between obesity/BMI and SSI not reported or raw data not provided to calculate risks [44,47,[50][51][52][53], and analyses restricted to deep wound infections [54,55].…”
Section: Literature Search and Systematic Review Resultsmentioning
confidence: 99%
“…Five additional potentially relevant studies were identified from reference lists. Of the 34 articles that underwent full-text review, 12 [22][23][24][25][26][27][28][29][30][31][32][33] met eligibility criteria for inclusion in the meta-analysis and 22 were excluded. The most common reasons for exclusion of the 22 studies were: criteria for the diagnosis of SSI not reported and/or CDC/NNIS criteria not applied [34][35][36][37][38][39][40][41][42][43][44][45][46][47], non-scalar definitions of obesity used [47][48][49], risk estimates of the association between obesity/BMI and SSI not reported or raw data not provided to calculate risks [44,47,[50][51][52][53], and analyses restricted to deep wound infections [54,55].…”
Section: Literature Search and Systematic Review Resultsmentioning
confidence: 99%
“…SSI ranges from 1.9% to 5.5% in most large series [11,13,14,19,22]. MIS has been postulated to reduce SSI rates [10].…”
Section: Discussionmentioning
confidence: 99%
“…Continuous variables analyzed includes patient's age, body mass index (BMI), length of operation, duration of hospitalization, number of intervertebral levels operated on, preoperative glucose levels, and estimated blood loss. These risk factors were chosen based on the previous literature evaluating SSI in spinal surgeries [7,10,11,16].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, patients who are obese may have difficulties with surgical access and there have been reports of an increased risk of operative complications for surgical procedures such as spinal surgery [4,6,8,17,22,23,29,35]. Some studies reported that obesity has been associated with unfavorable surgical outcomes such as longer operative times, greater operative blood loss, and a higher rate of revision for patients having spinal surgery [10,14,31,32,35,39].…”
Section: Introductionmentioning
confidence: 99%